A mass estimate of perfluoroalkyl substance (PFAS) release from Australian wastewater treatment plants. (October 2018) - Gallen, C.; Eaglesham, G.; Drage, D.; Nguyen, T. Hue; Mueller, J.F.
Abstract: Perfluoroalkyl substances (PFASs) have been used in large quantities for a variety of applications in Australian industry and household products. Through the course of their everyday use, PFASs enter the wastewater stream however current treatment processes provide only partial removal of these chemicals from wastewater. The release of treated effluent and re-use of biosolids represents an important point source of PFASs into the Australian environment yet the scale of PFAS release from Australian WWTPs is unknown. For the first time, influent, effluent and biosolids samples from 14 WWTPs across Australia were assessed for 9 PFASs and the national loads of these PFASs released from WWTPs estimated. Ʃ9PFASs ranged from 0.98 to 440 ng/L (influent), 21–560 ng/L (effluent) and 5.2–150 ng/g (biosolids). National loads of PFOA and PFOS in effluent were estimated at 65 kg and 26 kg per annum respectively. In biosolids, annual loads were estimated at 2 kg and 8 kg respectively. The continued detection of PFOS over a decade after its phase out, the increasing use of PFOS alternatives together with their resistance to degradation processes suggests that PFASs will be a priority for regulators and waste management to prevent further contamination of Australia's water resources. Highlights: PFASs were detected in the influent, effluent and biosolids of all 14 studied WWTPs. Ʃ9PFASs were elevated by an average of 9.8 times in effluent compared to influent. PFOA, PFOS detected in 93% and 86% of effluent samples (maximums 48 ng/L, 240 ng/L). PFOS (mean 25 ng/g) and PFDA (mean 17 ng/g) were most abundant in biosolids. National loads of PFOA and PFOS released by WWTPs were 67 kg and 33 kg annually.